2019
DOI: 10.1242/jeb.188573
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two genes: divergent evolutionary fate of haptoglobin and hemopexin in hemoglobinless antarctic icefishes

Abstract: The evolution of Antarctic notothenioid fishes in the isolated freezing Southern Ocean has led to remarkable trait gains and losses. One of the most extraordinary was the loss of the major oxygen carrier hemoglobin (Hb) in the icefishes (family Channichthyidae). Although the mechanisms of this loss and the resulting compensatory changes have been well studied, the impact of Hb loss on the network of genes that once supported its recycling and disposal has remained unexplored. Here, we report the functional fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Adding to the physiological calculus are mutations of key erythroid genes in the genomes of these fishes. We and others have identified lossof-function alleles in the alpha-and beta-globins [8][9][10], alas2, hemgn, haptoglobin [16] and myoglobin [12] that have risen to fixation in some, if not all, icefish species. These mutations are likely to constrain the adaptive landscape of icefishes and to render impossible the re-evolution of erythroid function as the SO warms.…”
Section: Plos Geneticsmentioning
confidence: 91%
See 1 more Smart Citation
“…Adding to the physiological calculus are mutations of key erythroid genes in the genomes of these fishes. We and others have identified lossof-function alleles in the alpha-and beta-globins [8][9][10], alas2, hemgn, haptoglobin [16] and myoglobin [12] that have risen to fixation in some, if not all, icefish species. These mutations are likely to constrain the adaptive landscape of icefishes and to render impossible the re-evolution of erythroid function as the SO warms.…”
Section: Plos Geneticsmentioning
confidence: 91%
“…Myoglobin expression is also absent from the hearts of 6 out of 16 icefish species, although mutated myoglobin genes remain in their genomes [12][13][14][15]. Furthermore, several genes encoding hemoglobin scavenging proteins, such as haptoglobin, have accumulated deleterious mutations and are expressed at reduced levels by icefishes [16]. Early work by Hureau et al [17] and by Barber et al [18] revealed that icefishes possess small numbers of…”
Section: Introductionmentioning
confidence: 99%
“…We also show that hemopexin (Hx) protein is reduced in the WMM of icefish. It was previously shown that Hx transcription occurs at levels comparable to those in the red-blooded notothenioids; however, it seems possible that there is a discrepancy between transcript and protein levels of Hx [ 80 ]. Cytochrome c oxidase (CO) is an important haem-containing protein just like haemoglobin and in our study was also found to be much reduced in icefish RMM.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with hundreds of red blooded notothenioids, these ice fish have very little Hp and its translation into a functional protein has actually been silenced [128]. Overtime, a degeneration of the Hp genotype manifested in a separate lineage.…”
Section: Divergent Evolutionary Fate Of Hp and Hpx Reveals The Potentmentioning
confidence: 99%